Addressing the Skills Gap: A Regional Analysis - Christo-Baker, E. Anne; Sindone, Anthony; Roper, Carolyn (Journal of Applied Business and Economics, 2017)
In the current volatile economic climate, job requirements and corresponding skill sets are also changing. This is evidenced by the apparent contradiction that while real unemployment rates for certain occupations remain high, jobs are left unfilled due to a lack of applicants with the requisite qualifications to fill them. Moreover, changes in existing jobs pose challenges for modifying existing skill sets. In order to stay competitive, organizational leaders and managers need to utilize effectively their investments in human capital. Using the case of Northwest Indiana (NWI), this study examines the current skills gap and solutions for closing it.